LAMINATE AND METHOD FOR MANUFACTURING LAMINATE

JP7651847B2Active Publication Date: 2025-03-27MITSUBISHI CHEM CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2020198990
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-11-30
Publication Date
2025-03-27
Estimated Expiration
2040-11-30

AI Technical Summary

Benefits of technology

【0007】 本発明では、積層体の最表面にリンクル(wrinkle)構造の凹凸を形成し、樹脂層に粒子を特定量添加することで、粒子の凝集を抑えながら積層体の表面凹凸形状を制御できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651847000002
    Figure 0007651847000002
  • Figure 0007651847000003
    Figure 0007651847000003
  • Figure 0007651847000004
    Figure 0007651847000004
Patent Text Reader

Abstract

To control the uneven surface shape of a laminate.SOLUTION: A laminate has a substrate 11, and a resin layer 12 and a cover layer 13 provided on at least one side 11A of the substrate 11. When the total solid content in the resin layer 12 is 100 mass%, the content of organic particles or inorganic particles is 1-25 mass%. The outermost surface 10A of the laminate 10 on one side 11A of the substrate 11 has irregularities having a wrinkled structure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate having an uneven surface, and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Conventionally, techniques for forming minute irregularities on the surfaces of various materials have been developed. For example, in packaging materials, it is known to form irregularities on the lid material or the inner peripheral surface of the container in order to prevent the contents from adhering to the material. In addition, a technique is also known in which fine irregularities are formed on optical materials to increase the haze and suppress transmission or surface reflection. For each of these applications, there is an optimum surface unevenness structure, and the unevenness structure is formed by controlling it.

[0003] Patent Document 1 discloses a water-repellent laminate comprising, in this order, a substrate, an organic solvent-resistant sealant film layer, and an anti-adhesion layer, the anti-adhesion layer containing a thermoplastic resin, water-repellent fine particles, and bead particles having an average particle size larger than that of the water-repellent fine particles. It has been shown that such a laminate has an anti-adhesion layer that contains two types of particles of different sizes, which forms a unique uneven structure on the surface, thereby significantly improving the anti-adhesion and water repellency of viscous contents. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2017-226199 A Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 does not specifically disclose a method for controlling the concave-convex structure, and further improvements are required for controlling the concave-convex structure. Therefore, an object of the present invention is to control the surface irregularities in a laminate. [Means for solving the problem]

[0006] The gist of the present invention is as follows: [1] to

[12] [1] A laminate comprising a substrate, and a resin layer and a cover layer provided on at least one surface of the substrate, The resin layer contains organic particles or inorganic particles in an amount of 1 to 25% by mass when the total solid content in the resin layer is taken as 100% by mass, A laminate in which the outermost surface of the laminate on the one surface side of the base material has irregularities including a wrinkle structure. [2] The laminate according to the above [1], wherein the specific surface area (S / A) of the outermost surface is 1.05 or more. [3] The laminate according to the above [1] or [2], wherein the outermost surface has an arithmetic mean roughness (Sa) of 1000 nm or more. [4] The laminate according to any one of the above [1] to [3], wherein the outermost surface has a Sz (maximum height) of 10,000 nm or more. [5] The laminate according to any one of the above [1] to [4], wherein the cover layer is an inorganic substance-containing layer. [6] The laminate according to the above [5], wherein the inorganic substance-containing layer is formed from at least one material selected from the group consisting of diamond-like carbon, metal, metal oxide, metal nitride, metal carbide, and composites thereof. [7] The laminate according to any one of the above [1] to [6], wherein the cover layer has a thickness (ta) of 5 nm or more and 300 nm or less. [8] The laminate according to any one of the above [1] to [7], wherein the resin layer has a thickness (tb) of 0.1 μm or more and 15 μm or less. [9] The laminate according to any one of the above [1] to [8], wherein the organic particles or inorganic particles have an average particle size of 1 μm or more and 30 μm or less.

[10] A step of applying a curable resin composition to at least one surface of a substrate to form a resin layer precursor; and further performing a surface treatment on the semi-cured or uncured resin layer precursor by a dry process to form a cover layer, thereby forming irregularities including a wrinkle structure on the surface of one side of the base material. The method for producing a laminate, wherein the curable resin composition contains organic particles or inorganic particles in an amount of 1 to 25% by mass when the total amount of solids in the curable resin composition is taken as 100% by mass.

[11] The method for producing a laminate according to the above

[10] , wherein the surface treatment is any one of chemical vapor deposition, physical vapor deposition, and plasma treatment.

[12] A step of semi-curing the resin layer precursor formed by the coating, The method for producing a laminate according to

[10] or

[11] , wherein the surface treatment is performed on the semi-cured resin layer precursor. Effect of the Invention

[0007] In the present invention, by forming irregularities with a wrinkle structure on the outermost surface of the laminate and adding a specific amount of particles to the resin layer, it is possible to control the surface irregularity shape of the laminate while suppressing particle aggregation. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a laminate of the present invention. [Diagram 2] 1 is a schematic diagram showing an example of a laminate of the present invention. [Diagram 3] 1 is an image of the outermost surface of the laminate having projections and recesses in Example 1, observed at 1,000 times magnification using a scanning electron microscope (SEM). [Figure 4] 1 is an image of the outermost surface of the laminate having projections and recesses in Example 2, observed at 1,000 times magnification using a scanning electron microscope (SEM). [Diagram 5] 1 is an image of the outermost surface of the laminate having projections and recesses in Example 3, observed at 1,000 times magnification using a scanning electron microscope (SEM). [Figure 6] 1 is an image of the outermost surface of the laminate having projections and recesses in Example 4, observed at 1,000 times magnification using a scanning electron microscope (SEM). [Figure 7] 1 is an image of the outermost surface of the laminate having projections and recesses in Comparative Example 1, observed at 1,000 times magnification using a scanning electron microscope (SEM). [Figure 8] 1 is an image of the outermost surface of the laminate having projections and recesses in Comparative Example 2, observed at 1,000 times magnification using a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Next, the present invention will be described in detail based on the embodiments of the present invention, but the present invention is not limited to the embodiments described below.

[0010] A laminate 10 according to one embodiment of the present invention has a substrate 11, and a resin layer 12 and a cover layer 13 provided on at least one surface 11A of the substrate 11, as shown in FIG. 1, and contains 1 to 25 mass% of organic particles or inorganic particles when the total amount of solids in the resin layer 12 is taken as 100 mass%. In the laminate 10, the resin layer 12 may be formed on the substrate 11 so as to be in direct contact with the substrate 11, or a layer such as an adhesive layer may be appropriately provided between the substrate 11 and the resin layer 12. The laminate of the present invention will be described in more detail below.

[0011] <Unevenness including wrinkle structure> In the laminate 10, the outermost surface 10A of the laminate 10 on one surface 11A side of the base material 11 has unevenness including a wrinkle structure. The laminate 10 has irregularities including a wrinkle structure, and is therefore applicable to various applications that utilize the fine irregularities on the surface (such as adhesion prevention and light transparency). For example, if a liquid-repellent material is selected for the layer constituting outermost surface 10A of laminate 10, contents will not easily adhere to the surface of the laminate, making it applicable to packaging materials. Furthermore, if the adhesion of cells, bacteria, etc. can be reduced by controlling the uneven structure, it may be possible to apply the material to sanitary materials. Furthermore, by having unevenness including a wrinkle structure, good cloudiness can be achieved, and for example, the haze and light transmittance of the laminate can be controlled.

[0012] Here, the wrinkle structure refers to a wrinkled shape caused by buckling of the resin layer 12, and is different from an uneven shape with many dot-like protrusions, such as an uneven shape formed only by particles. Since the wrinkle structure of this embodiment is formed spontaneously, a mold such as a transfer sheet is not required.

[0013] A schematic diagram of the wrinkle structure is shown in Figure 2. The wrinkle structure is composed of a plurality of ripples c, and each of the plurality of ripples c has a protrusion a and a groove b. The protrusion a and the groove b each have a straight line, a curved line, or a combination of these. The protrusion a is formed irregularly. The protrusion a may be formed continuously or discontinuously.

[0014] As described below, the wrinkle structure is formed when compressive stress is applied along the surface direction to the resin layer 12. It is presumed that the compressive stress is applied along multiple directions along the surface direction, which results in the irregular formation of the protrusions a and grooves b. The presence or absence of a wrinkle structure can be confirmed by observing the outermost surface of the laminate with a microscope such as a scanning electron microscope (SEM) at a magnification of, for example, about 1,000 to 100,000 times (see Figs. 3 to 8). When a wrinkle structure is present, the protrusions a and grooves b are observed to form undulations c. The undulations c can be observed in a square or rectangular observation image with one side measuring, for example, about 3 to 500 µm, preferably about 4 to 100 µm. The protrusions a forming the wrinkle structure are irregular, and the undulations c also appear at a period on the order of micrometers. Therefore, as shown in Figures 3 to 6, the undulations c formed by the protrusions a and grooves b appear as multiple peaks of the protrusions a and multiple bottoms of the grooves b (e.g., five or more times) even when viewed in multiple directions (e.g., three directions) such as the vertical, horizontal, and diagonal directions in the observed image. The period of the undulations c is typically not constant, and therefore the distance between the peaks of the protrusions a and the distance between the bottoms of the grooves b are also not constant. The "period of waviness c" refers to the distance d between the apex of a protrusion a and the apex of the protrusion a adjacent to a groove b adjacent to the protrusion a, as shown in FIG.

[0015] The fact that the unevenness of outermost surface 10A of laminate 10 has a spontaneously formed wrinkle structure is reflected in, for example, the value of Ssk (skewness). Ssk is a parameter that indicates the degree of deviation of the surface unevenness. This deviation Ssk represents the cube mean of Z(x,y) on a reference plane that has been made dimensionless by the cube of the root-mean-square height Sq, and means skewness, a value that indicates the symmetry of the peaks and valleys centered on the average plane. Therefore, when the deviation Ssk<0, it means that there is a downward deviation from the average line, that is, there are more concave valleys than convex peaks. On the other hand, when Ssk>0, it means that there is an upward deviation from the average line, that is, there are more convex peaks than concave valleys. And when the deviation Ssk=0, it means that there is symmetry (normal distribution) with respect to the average line.

[0016] The wrinkle structure of the outermost surface 10A of the laminate 10 of the present invention is a wrinkled shape caused by buckling of the resin layer 12. Therefore, compared to an uneven shape formed only by particles, the symmetry of the convex peaks and concave valleys is higher. Therefore, it is considered that the Ssk of the wrinkle structure of the laminate 10 of the present invention is closer to 0 than the Ssk of an uneven shape formed only by particles. From this viewpoint, the absolute value of Ssk of the outermost surface 10A of the laminate 10 is preferably 5 or less, more preferably 3 or less, even more preferably 1 or less, and even more preferably 0.8 or less. Among these, it is preferably 0.6 or less.

[0017] Ssk is a parameter based on ISO25178 and can be calculated, for example, by the following method. A three-dimensional non-contact surface shape measuring device (VertScan2.0 R5200G, manufactured by Ryoka Systems Co., Ltd.) was used to perform measurements with a CCD camera SONY HR-50 1 / 3 inch (10x objective lens, 530nm white wavelength filter) in measurement mode: Wave, and measurement area: 469.17μm x 351.89μm. The attached analysis software (VS-Viewer Version 5.1.3) was used to remove the waviness components from the captured image using polynomial fourth-order approximation surface correction, and then interpolation processing (a process in which pixels for which height data could not be obtained are supplemented with height data calculated from surrounding pixels) was performed to calculate the height.

[0018] The dispersion state of the particles in the resin layer 12 appears, for example, in the Sku (kurtosis) value. Sku is a parameter that indicates the sharpness of surface irregularities. This sharpness Sku is a value that represents the fourth-mean of Z(x) in a reference length that has been non-dimensionalized by the fourth power of the root-mean-square height Sq. When Sku>3, it means that the convex peaks and concave valleys are sharp. On the other hand, when Sku<3, it means that the convex peaks and concave valleys are round. And when Sku=3, it means that the convex peaks and concave valleys are normally distributed.

[0019] When the particles in the resin layer 12 are dispersed, the particle portions form peaks that are sharper than the protrusions a of the wrinkle structure. On the other hand, when the particles in the resin layer 12 are aggregated, the aggregated particles form peaks that are rounder than the protrusions a of the wrinkle structure, and in the portions without particles, the wrinkle structure is partially prevented from being formed, and flatter (rounder) valleys than the grooves b of the wrinkle structure are formed. Thus, it is considered that the Sku of the outermost surface 10A of the laminate 10 of the present invention increases as the particles are more dispersed, and decreases as the particles are more aggregated. From this viewpoint, Sku of the outermost surface 10A of the laminate 10 is preferably 2.8 or more, more preferably 2.9 or more, even more preferably 2.92 or more, and even more preferably 3 or more. There is no particular upper limit, but it is sufficient as long as it is 4 or less, and more preferably 3.5 or less.

[0020] Sku is a parameter based on ISO25178 and can be calculated in the same way as Ssk above.

[0021] The outermost surface 10A of the laminate preferably has a specific surface area (S / A) of 1.05 or more. By making the specific surface area 1.05 or more, it means that the surface area is sufficiently large due to the wrinkle structure and the addition of particles. Therefore, in optical applications, cloudiness is easily manifested, and the haze value of the laminate can be adjusted by adjusting the specific surface area. From these viewpoints, the specific surface area (S / A) is more preferably 1.1 or more, and further preferably 1.12 or more. In addition, the specific surface area (S / A) is not particularly limited, but in order to prevent the protrusions of the wrinkle structure from becoming too high, which would reduce the structural strength, it is preferably 2 or less, more preferably 1.7 or less, and even more preferably 1.5 or less. The specific surface area (S / A) can be calculated by S / A, where A is the area of ​​the measurement target area on the outermost surface 10A and S is the surface area of ​​the measurement target area. More specifically, it can be determined by the method shown in the examples described later.

[0022] The Sa (arithmetic mean roughness) of the outermost surface 10A of the laminate is not particularly limited, but is, for example, 1000 nm or more. By making Sa 1000 nm or more, it means that sufficient unevenness is formed by adding wrinkle structure and particles, and for example, if applied to optical materials, the haze can be adjusted. From these viewpoints, Sa (arithmetic mean roughness) is preferably 1200 nm or more, more preferably 1500 nm or more, even more preferably 1800 nm or more, and even more preferably 2000 nm or more. Furthermore, the arithmetic mean roughness Sa is not particularly limited, but from the viewpoint of maintaining the physical strength of the wrinkle structure, it is preferably 10,000 nm or less, more preferably 5,000 nm or less, and even more preferably 3,000 nm or less.

[0023] The Sz (maximum height) of the outermost surface 10A of the laminate is not particularly limited, but is preferably 10000 nm or more, more preferably 12000 nm or more, and even more preferably 15000 nm or more. If Sz is equal to or greater than these lower limits, it means that sufficient buckling has progressed and a wrinkle structure with high protrusions has been formed. Therefore, if it is applied to an optical material, for example, the haze can be adjusted. Although there are no particular limitations on Sz (maximum height), from the viewpoint of maintaining the physical strength of the wrinkle structure, it is preferably 50,000 nm or less, and more preferably 30,000 nm or less. Incidentally, Sa and Sz can be measured by the method shown in the examples described later.

[0024] <Base material> The substrate used in the laminate of the present invention is not particularly limited, and examples of the material include organic substances such as resins, inorganic substances such as metals and metal oxides, and organic-inorganic composites. Examples of the shape of the substrate include sheets, films, substrates, and three-dimensional objects including containers and tubes. The substrate of the present invention is preferably made of a resin, and more preferably a resin film or a plastic container. The laminate of the present invention can easily form unevenness even on a substrate having a complex shape or on the inside of a container, by the manufacturing method described below.

[0025] [Resin film] The resin film used as the substrate is not limited in material and structure as long as it has necessary and sufficient rigidity. The resin film may be a single-layer structure or a multi-layer structure. When the resin film has a multi-layer structure, it may be a four-layer or more multi-layer structure in addition to a two-layer or three-layer structure as long as it does not impair the effects of the present invention.

[0026] Examples of resins used in the resin film include polyester, polyarylates, polyethersulfone, polycarbonate, polyetherketone, polysulfone, polyphenylene sulfide, polyester-based liquid crystal polymer, triacetyl cellulose, cellulose derivatives, polypropylene, polyamides, polyimide, polycycloolefins, etc. These resins may be used alone or in combination of two or more in the resin film. In addition, when the resin film is multi-layered, the resins constituting each layer may be different from each other or may be the same as each other. In addition, the resin film may be a single layer or a multilayer film, with each layer being constituted by combining two or more of the above-mentioned resins.

[0027] Whether the resin film has a single layer structure or a multi-layer structure, it is preferable that the resin film is a polyester film in which the main component resin of each layer is polyester. In this case, the "main component resin" means the resin that is contained in the largest proportion among the resins constituting the polyester film, for example, a resin that accounts for 50 mass% or more, preferably 70 mass% or more, and more preferably 80 mass% or more (including 100 mass%) of the resins constituting the polyester film. As long as each layer of the resin film contains polyester as a main component resin, it may contain a resin other than polyester or a component other than resin.

[0028] The polyester may be a homopolyester or a copolymer polyester. In the case of a homopolyester, it is preferable that the polyester is obtained by polycondensation of an aromatic dicarboxylic acid and an aliphatic glycol. Examples of the aromatic dicarboxylic acid include terephthalic acid and 2,6-naphthalenedicarboxylic acid. Examples of the aliphatic glycol include ethylene glycol, diethylene glycol, and 1,4-cyclohexanedimethanol.

[0029] On the other hand, examples of the dicarboxylic acid component of the copolymer polyester include one or more of isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalenedicarboxylic acid, sebacic acid, etc., and examples of the glycol component include one or more of ethylene glycol, diethylene glycol, propylene glycol, butanediol, 4-cyclohexanedimethanol, neopentyl glycol, etc.

[0030] Specific examples of polyester include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), and polybutylene naphthalate (PBN). Of these, PET and PEN are preferred, and PET is more preferred.

[0031] The resin film may contain particles for the purpose of forming a fine uneven structure on the film surface to impart various functions and for the main purpose of preventing the occurrence of scratches in each process. The type of the particles is not particularly limited as long as they are particles that can provide easy slipping. For example, inorganic particles such as silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide, and organic particles such as acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin can be mentioned. These can be used alone or in combination of two or more. Furthermore, precipitated particles obtained by precipitating and finely dispersing a part of a metal compound such as a catalyst in a process for producing a resin component such as polyester can also be used. The shape of the particles is not particularly limited. For example, it may be any of spherical, blocky, rod-like, flat, etc. Furthermore, the hardness, specific gravity, color, etc. of the particles are also not particularly limited. Two or more kinds of these particles may be used in combination as necessary.

[0032] The average particle size of the particles is preferably 5 μm or less, more preferably 0.01 μm to 3 μm, and even more preferably 0.5 μm to 2.5 μm. By making the particle size 5 μm or less, the surface roughness of the resin film is prevented from becoming rough, and problems are less likely to occur when forming the resin layer and the cover layer.

[0033] The particle content is preferably 5% by mass or less, more preferably 0.0003% by mass or more and 3% by mass or less, and even more preferably 0.01% by mass or more and 2% by mass or less, based on 100% by mass of the resin film. By setting the particle content in this range, it is possible to achieve both smoothness and transparency of the film.

[0034] The method of adding particles to the resin film is not particularly limited, and any conventionally known method can be used. For example, the particles can be added during the process of producing the resin component. For example, in the case of a polyester film, the particles can be added at any stage of polyester production. It is preferable to add the particles after the esterification or transesterification reaction is completed.

[0035] If necessary, conventionally known additives such as antioxidants, antistatic agents, heat stabilizers, lubricants, dyes, pigments, and ultraviolet absorbing agents may be added to the resin film.

[0036] The thickness of the resin film is not particularly limited as long as it is within the range in which a film can be formed, but is preferably 12 μm or more and 250 μm or less, more preferably 25 μm or more and 250 μm or less, and even more preferably 50 μm or more and 200 μm or less.

[0037] The resin film can be formed by, for example, forming a resin composition into a film shape by a melt casting method or a solution casting method. In the case of a multi-layer structure, it may be co-extruded. In addition, it may be uniaxially or biaxially stretched, and from the viewpoint of rigidity, a biaxially stretched film is preferable.

[0038] [Plastic containers] The plastic container used as the substrate in the present invention is not particularly limited, and may be a bottomed cylindrical container, or a container with a rounded bottom and an elliptical cross section. Also, it may be a container with a substantially rectangular cross section whose mouth is narrower than its body. The diameter of the mouth of the container may be narrower.

[0039] Examples of plastic materials that make up plastic containers include polyethylene terephthalate resin (PET), polyethylene terephthalate copolymer resin (copolymer resin using cyclohexanedimethanol or the like as a comonomer instead of ethylene glycol in the alcohol component of polyester), polybutylene terephthalate resin, polyethylene naphthalate resin, polyethylene resin, polypropylene resin (PP), cycloolefin copolymer resin (COC, cyclic olefin copolymer), ionomer resin, poly-4-methylpentene-1 resin, polymethyl methacrylate resin, polystyrene resin, ethylene-vinyl alcohol copolymer resin, acrylonitrile resin, polyvinyl chloride resin, polyvinylidene chloride resin, polyamide resin, polyamideimide resin, polyacetal resin, polycarbonate resin (PC), polysulfone resin, tetrafluoroethylene resin, acrylonitrile-styrene resin, acrylonitrile-butadiene-styrene resin, etc., and among these, polyethylene terephthalate resin (PET) and polycarbonate resin (PC) are preferred in terms of versatility.

[0040] [Substrates other than resin] The substrate other than resin is not particularly limited as long as a resin layer (described later) can be fixed onto the substrate, but examples of the substrate include metals, semi-metals, ceramics, and composite materials. Examples of metals include aluminum, copper, silver, gold, iron, and nickel. These metals may be used alone or in the form of an alloy. Preferred examples include aluminum, copper, and the steel-based material SUS. Examples of the semi-metal include silicon and germanium, and these semi-metals may be used alone or in the form of an alloy. Ceramics include inorganic solid materials such as oxides, carbides, nitrides, and borides, and preferably include glass, ceramics, and the like. A composite material is a material that is an integral combination of two or more different materials such as resin, metal, semi-metal, and ceramic, and examples of the composite material include glass fiber reinforced plastic, carbon fiber reinforced plastic, and nanocomposite material. As the substrate other than these resins, metal containers, glass containers, etc. are suitable.

[0041] <Resin layer> The resin layer is preferably formed from a heat or active energy ray curable resin composition (hereinafter, sometimes simply referred to as a "curable resin composition"). The resin layer is a cured product formed by curing the curable resin composition. By curing the curable resin composition, it can be easily adhered to a substrate, a cover layer, etc. Furthermore, as described below, when a surface treatment is performed by a dry process in a semi-cured state, it can buckle in response to a compressive stress acting along the surface direction to form a wrinkle structure.

[0042] [Thermosetting resin composition] When the curable resin composition is a thermosetting resin composition, the thermosetting resin composition preferably contains a binder resin, and more preferably contains a binder resin and a curing agent. By containing a binder resin and a curing agent, the thermosetting resin composition is likely to buckle when a compressive stress is applied, while ensuring adhesion to a substrate, a cover layer, etc., and is likely to form a wrinkle structure.

[0043] (binder resin) The binder resin is a thermosetting resin that can be cured by heating, and when the thermosetting resin composition contains a curing agent, the binder resin is a resin that is cured in the presence of the curing agent. Examples of the binder resin include polyester resin, urethane resin, acrylic resin, vinyl alcohol resin, ethylene vinyl alcohol resin, vinyl modified resin, oxazoline group-containing resin, carbodiimide group-containing resin, epoxy group-containing resin, isocyanate group-containing resin, alkoxyl group-containing resin, modified styrene resin, and modified silicone resin, which can be used alone or in combination of two or more. The binder resin may be reacted with another binder resin to form a resin layer. Among these, from the viewpoints of adhesion to the substrate or to the substrate and the cover layer, and hot water resistance, it is preferable to use at least one resin selected from polyester resins, urethane resins, acrylic resins, epoxy group-containing resins, and alkoxyl group-containing resins, either alone or in combination, and acrylic resins are more preferable. The binder resin may be any resin capable of thermal crosslinking, such as urethane curing or epoxy curing, and from the viewpoint of reactivity with an isocyanate compound used as a curing agent described later, it is preferable that the binder resin is a polyol having two or more hydroxyl groups in one molecule, and among these, an acrylic polyol is preferable.

[0044] Examples of acrylic resins include (meth)acrylic polymers obtained by polymerizing polymerizable monomers including (meth)acrylic monomers. The (meth)acrylic polymers may be homopolymers or copolymers, or may be copolymers with polymerizable monomers other than (meth)acrylic monomers. The (meth)acrylic monomer is a monomer having a (meth)acryloyl group. The polymerizable monomer other than the (meth)acrylic monomer is a monomer having a polymerizable functional group, and the polymerizable functional group may be a functional group having a carbon-carbon unsaturated bond other than the (meth)acryloyl group, such as a vinyl group. In this specification, when the expression "(meth)acryloyl group" is used, it means one or both of "acryloyl group" and "methacryloyl group", and the same applies to other similar terms.

[0045] Examples of the polymerizable monomer include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, pentadecyl (meth)acrylate, and dodecyl (meth)acrylate; cyclic alkyl (meth)acrylates such as cyclohexyl (meth)acrylate and isobornyl (meth)acrylate; and hydrocarbon (meth)acrylates in which the portion other than the polymerizable functional group is composed of a hydrocarbon, such as (meth)acrylates having an aromatic ring, such as phenyl (meth)acrylate. Among these, alkyl (meth)acrylates or cyclic alkyl (meth)acrylates are preferred, with methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate being more preferred, and with methyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and cyclohexyl (meth)acrylate being even more preferred. In the (meth)acrylic polymer, the content of structural units derived from a hydrocarbon-based (meth)acrylate is preferably, for example, from 20% by mass to 90% by mass, or from 30% by mass to 80% by mass.

[0046] As the polymerizable monomer, a monomer component other than a hydrocarbon-based (meth)acrylate may be used, and specifically, a hydroxyl group-containing monomer is preferably used. As the hydroxyl group-containing monomer, for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 6-hydroxyhexyl (meth)acrylate can be mentioned. The hydroxyl group in the hydroxyl group-containing monomer is a hydroxyl group that is not directly bonded to an aromatic ring. Among these, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate are preferred. The hydroxyl group-containing monomer is preferably used in combination with the above-mentioned hydrocarbon-based (meth)acrylate, and therefore the acrylic resin is preferably a (meth)acrylic copolymer obtained by copolymerizing a hydrocarbon-based (meth)acrylate with a hydroxyl group-containing monomer, or a (meth)acrylic copolymer obtained by copolymerizing a hydrocarbon-based (meth)acrylate with a hydroxyl group-containing monomer and a monomer component other than these (other monomer components). This allows the (meth)acrylic copolymer to be an acrylic polyol containing multiple hydroxyl groups. In the (meth)acrylic polymer, the content of the structural units derived from the hydroxyl group-containing monomer is, for example, preferably from 0.5% by mass to 80% by mass, and more preferably from 1% by mass to 70% by mass.

[0047] As the polymerizable monomer, a monomer component (other monomer component) other than the hydrocarbon-based (meth)acrylate and the hydroxyl group-containing monomer may be used. Specifically, a carboxyl group-containing monomer such as acrylic acid, methacrylic acid, crotonic acid, itaconic acid, fumaric acid, maleic acid, or citraconic acid; an amino group-containing monomer such as dimethylaminoethyl (meth)acrylate, dimethylaminoethyl (meth)methacrylate, or diethylaminoethyl (meth)acrylate; glycidyl (meth)acrylate, β-methylglycidyl (meth)acrylate, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, or α-methyl-o-vinylbenzyl glycidyl Examples of suitable monomers include epoxy group-containing monomers such as ether, α-methyl-m-vinylbenzyl glycidyl ether, α-methyl-p-vinylbenzyl glycidyl ether, and 3,4-epoxycyclohexylmethyl (meth)acrylate; alkylene glycol monoalkyl ether (meth)acrylates such as ethylene glycol monomethyl ether acrylate and ethylene glycol monomethyl ether methacrylate; acrylamide compounds such as (meth)acrylamide, diacetone acrylamide, and N-methylol acrylamide; (meth)acrylonitrile; styrene derivatives such as styrene, α-methylstyrene, divinylbenzene, and vinyltoluene; and various vinyl halides such as vinyl chloride and vinylidene chloride. In addition, the polymerizable monomer may be a monomer having a functional group with an ultraviolet absorbing function from the viewpoint of improving the light resistance of the resin layer, etc. Specific examples include monomers having an ultraviolet absorbing functional group such as a benzotriazole skeleton, a benzophenone skeleton, a triazine skeleton, or a hindered amine skeleton, and a polymerizable functional group such as a (meth)acryloyl group.

[0048] The content of structural units derived from other monomer components (monomer components other than hydrocarbon (meth)acrylates and hydroxyl group-containing monomers) in the (meth)acrylic polymer is, for example, 50% by mass or less, preferably 40% by mass or less. There is no particular lower limit, and it may be 0% by mass or more. As exemplified above, each of the above monomer components (hydrocarbon (meth)acrylate, hydroxyl group-containing monomer, and other monomer components) is preferably a monofunctional monomer having one polymerizable functional group in the molecule, but may appropriately contain a polyfunctional monomer having two or more polymerizable functional groups within a range that does not impair the effects of the present invention.

[0049] (hardening agent) As the curing agent, a compound capable of reacting with the binder resin and curing may be used, but from the viewpoint of curability with the binder resin, an isocyanate compound is preferably used. When an isocyanate compound is used, the binder resin should have a functional group capable of reacting with an isocyanate group, and examples of the functional group include a hydroxyl group, a carboxyl group, and an amino group, and from the viewpoint of reactivity with an isocyanate group, a hydroxyl group is preferred. Therefore, it is preferable to use an isocyanate compound as a curing agent and a polyol as a binder resin, and when an acrylic resin is used, the acrylic resin is preferably an acrylic polyol containing multiple hydroxyl groups in one molecule as described above.

[0050] The isocyanate compound is preferably an aromatic or aliphatic diisocyanate or a trivalent or higher polyisocyanate. Examples of the isocyanate compound that can be used include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, cyclohexane diisocyanate, dicyclohexyl diisocyanate, and trimers thereof. Also, a terminal isocyanate group-containing compound obtained by reacting an excess amount of these isocyanate compounds with, for example, low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, trimethylolpropane, glycerin, sorbitol, biuret, cyanuric acid, ethylenediamine, monoethanolamine, diethanolamine, and triethanolamine, or active hydrogen polymer compounds such as polyester polyol, polyether polyol, and polyamide, may be used.

[0051] (Ratio of each ingredient) In the thermosetting resin composition, the blending ratio of the binder resin and the curing agent may be adjusted by mixing the ratio of the number of hydroxyl groups in the binder resin to the number of isocyanate groups in the curing agent, and (the number of isocyanate groups) / (the number of hydroxyl groups) is preferably 0.05 or more and 30 or less, more preferably 0.1 or more and 20 or less, and even more preferably 0.2 or more and 15 or less.

[0052] (Preferred form of thermosetting resin composition) When the resin layer is formed from a thermosetting resin composition, the resin layer preferably contains a resin having a urethane bond. By using a resin having a urethane bond, flexibility is ensured and the resin layer is prone to buckling due to compressive stress generated when the surface is treated by a dry process. The urethane bond is preferably formed by at least one of the reaction between the binder resins and the reaction between the binder resin and the curing agent, and more preferably by the reaction between the binder resin and the curing agent. When the urethane bond is formed by such a reaction, the adhesion of the resin layer to the cover layer, the substrate, etc. is easily improved. From the viewpoints of promoting the curing with the binder resin and the above-mentioned adhesion, it is preferable to use an isocyanate compound as a curing agent.

[0053] [Active energy ray-curable resin composition] (Photopolymerizable compound) When the curable resin composition is an active energy ray curable resin composition, the active energy ray curable resin composition contains a photopolymerizable compound. The photopolymerizable compound is a compound that can be polymerized by being irradiated with active energy rays. Details of the active energy rays are as described in the production method described later. The resin component of the resin layer formed from the active energy ray-curable resin composition can be a mixture of a prepolymer such as epoxy (meth)acrylate, urethane (meth)acrylate, polyester (meth)acrylate, or acrylic (meth)acrylate with a photopolymerizable monomer, or the photopolymerizable monomer can be used alone.

[0054] The photopolymerizable monomer is not particularly limited as long as it is a compound having a radical polymerizable group, and examples thereof include polyfunctional photopolymerizable monomers. The number of radical polymerizable groups contained in one molecule of the polyfunctional photopolymerizable monomer is not particularly limited, and may be 2 or more. The radically polymerizable group includes functional groups containing a carbon-carbon unsaturated bond, such as a (meth)acryloyl group and a vinyl group, and among these, a (meth)acryloyl group is preferred.

[0055] Examples of the photopolymerizable monomer include polyfunctional (meth)acrylates having an aromatic ring. Specifically, polyfunctional (meth)acrylates having a benzene ring, a naphthalene ring, an anthracene ring, a fluorene ring, a phenanthrene ring, a phenalene ring, or the like are preferred. Among these, fluorene-based polyfunctional (meth)acrylates having a fluorene ring are preferred. Examples of fluorene-based polyfunctional (meth)acrylates include 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene, 9,9-bis[4-(2-(meth)acryloyloxyethoxy)-3-methylphenyl]fluorene, 9,9-bis[4-(2-(meth)acryloyloxypropoxy)-3-methylphenyl]fluorene, and 9,9-bis[4-(2-(meth)acryloyloxyethoxy)-3,5-dimethylphenyl]fluorene. , 9,9-bis[4-((meth)acryloyloxypoly(ethyleneoxy))phenyl]fluorene, 9,9-bis[4-((meth)acryloyloxypolyethyleneoxy)-3-methylphenyl]fluorene, 9,9-bis[4-((meth)acryloyloxypoly(propyleneoxy))-3-methylphenyl]fluorene, 9,9-bis[4-((meth)acryloyloxypoly(ethyleneoxy))-3,5-dimethylphenyl]fluorene, and the like.

[0056] In addition, as the photopolymerizable monomer, various polyfunctional (meth)acrylates can be used in addition to polyfunctional (meth)acrylates having an aromatic ring, and examples of such polyfunctional (meth)acrylates include aliphatic polyfunctional (meth)acrylates such as ethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tricyclodecane dimethanol di(meth)acrylate. The above-mentioned photopolymerizable monomers may be used alone or in combination of two or more kinds. Among the above, polyfunctional (meth)acrylates having an aromatic ring are preferred, and polyfunctional (meth)acrylates having an aromatic ring may be used in combination with other photopolymerizable compounds. The photopolymerizable monomer may be used alone or in combination with a monofunctional photopolymerizable compound described below.

[0057] The photopolymerizable monomer is not limited to a polyfunctional one, and may be a monofunctional photopolymerizable monomer. The monofunctional photopolymerizable monomer may be used alone, or may be used in combination with a polyfunctional photopolymerizable monomer as described above. Examples of the monofunctional photopolymerizable monomer include alkyl (meth)acrylates, cyclic alkyl (meth)acrylates, (meth)acrylates having an aromatic ring, hydroxyl group-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, epoxy group-containing monomers, acrylamide compounds, (meth)acrylonitrile, styrene derivatives, vinyl halides, etc. Specific examples of these compounds include those exemplified in the above-mentioned (meth)acrylic polymers.

[0058] (Photopolymerization initiator) When the curable resin composition contains a photopolymerizable compound, it is preferable that the curable resin composition further contains a photopolymerization initiator. By containing the photopolymerization initiator, the resin layer precursor can be easily cured by irradiating the resin layer precursor with active energy rays as described below. Examples of photopolymerization initiators include benzil, benzophenone and derivatives thereof, thioxanthones, benzil dimethyl ketals, α-hydroxyalkylphenones, α-hydroxyacetophenones, hydroxyketones, aminoalkylphenones, acylphosphine oxides, oxime ester compounds, etc. Among these, α-hydroxyalkylphenones are preferred because they are less likely to yellow during curing and can give a transparent cured product. The content of the photopolymerization initiator is preferably in the range of 0.05 to 5 parts by mass, more preferably 0.2 to 3 parts by mass, relative to 100 parts by mass of the curable resin composition. When the content of the photopolymerization initiator is 0.05 parts by mass or more, a desired initiation effect can be obtained, and when the content of the photoinitiator is 5 parts by mass or less, the curable resin composition is not over-cured by irradiation with active energy rays, and is easily maintained in a semi-cured state.

[0059] In the above description, the curable resin composition is described as being either heat-curable or active energy ray-curable, but it may be a heat- and active energy ray-curable resin composition that can be cured by both heat and active energy rays. In this case, the curable resin composition may contain both a binder resin and a photopolymerizable compound.

[0060] [Organic or inorganic particles] The curable resin composition of the present invention contains 1 to 25% by mass of organic particles or inorganic particles when the total solid content is taken as 100% by mass. When the particle content is 1% by mass or more, a wrinkle structure and a complex uneven structure due to the particles can be formed. On the other hand, when the particle content is 25% by mass or less, aggregation of the particles is unlikely to occur. From the above viewpoints, the particle content is preferably from 5% by mass to 23% by mass, more preferably from 8% by mass to 20% by mass, and even more preferably 15% by mass or less.

[0061] Examples of organic particles include acrylic resin, styrene resin, urea resin, phenol resin, epoxy resin, and benzoguanamine resin. Examples of inorganic particles include silica, calcium carbonate, magnesium carbonate, barium carbonate, calcium sulfate, calcium phosphate, magnesium phosphate, kaolin, aluminum oxide, and titanium oxide. These organic particles and inorganic particles may be used alone or in combination of two or more kinds. The shape of the particles is not particularly limited. For example, it may be any of spherical, blocky, rod-like, flat, etc. Furthermore, the hardness, specific gravity, color, etc. of the particles are also not particularly limited. Two or more kinds of these particles may be used in combination as necessary.

[0062] The average particle size of the particles is preferably 1 μm or more and 30 μm or less, more preferably 5 μm or more and 20 μm or less, and further preferably 10 μm or more. By setting the average particle size of the particles in this range, a wrinkle structure and a complex uneven structure due to the particles can be formed. From the above viewpoint, it is preferable that the average particle size of the particles is larger than the thickness of the resin layer. The average particle size of the particles can be measured by a method such as a light scattering method (single light scattering, laser diffraction / scattering).

[0063] The curable resin composition may contain, as necessary, an internal antifoaming agent, a coatability improving agent, a thickener, an organic lubricant, an ultraviolet absorber, an antioxidant, a foaming agent, a dye, a pigment, etc., within the scope of the present invention. These additives may be used alone, or two or more kinds may be used in combination as necessary.

[0064] [Resin layer thickness] The thickness (tb) of the resin layer may be adjusted according to the step of the unevenness to be formed and the application, but is preferably 0.1 μm or more and 15 μm or less. If it is 15 μm or less, peeling from the substrate due to the internal stress of the resin layer itself can be prevented. If it is 0.1 μm or more, the thickness of the resin layer can be kept uniform, and a certain level of roughness can be ensured by the wrinkle structure. From this viewpoint, the thickness (tb) of the resin layer is more preferably 0.5 μm or more, even more preferably 1 μm or more, even more preferably 2 μm or more, and is preferably 10 μm or less, more preferably 7 μm or less. The thickness of the resin layer and the cover layer described later can be calculated by measuring the maximum thickness (convex peaks) and minimum thickness (concave valleys) by step measurement using a microprofile measuring device or by cross-sectional observation using a scanning electron microscope (SEM) and / or a transmission electron microscope (TEM), and then calculating the average value of these.

[0065] <Cover layer> The laminate of the present invention has a cover layer on the resin layer. The cover layer may be formed as a layer that is in direct contact with the resin layer. Specific examples of the cover layer include an inorganic substance-containing layer and a cover resin layer. Among these, an inorganic substance-containing layer is preferred.

[0066] [Inorganic content layer] The inorganic substance-containing layer is a layer formed of an inorganic substance and contains an inorganic substance as a main component. Incidentally, containing an inorganic substance as a main component means that the inorganic substance occupies 50% by mass or more, particularly 70% by mass or more, particularly 80% by mass or more, particularly 90% by mass or more, particularly 100% by mass of the inorganic substance-containing layer. The inorganic substance-containing layer is preferably formed of an inorganic substance having good adhesion to the resin layer. In addition, the inorganic substance-containing layer is preferably formed using a material that can be easily formed on the resin layer by a dry process.

[0067] The inorganic material-containing layer is preferably formed from at least one inorganic material selected from diamond-like carbon (DLC), metal, metal oxide, metal nitride, metal carbide, or a composite thereof. The metal here also includes so-called semimetals such as silicon, boron, and germanium. In the inorganic substance-containing layer, examples of the metal constituting the metal, metal oxide, metal nitride, metal carbide, or a composite thereof include silicon, aluminum, zinc, titanium, niobium, gold, silver, copper, indium, tin, nickel, and the like. Among these, silicon and niobium are preferred, and silicon is more preferred.

[0068] The inorganic material used in the inorganic material-containing layer is preferably at least one selected from silicon-based compounds such as silicon oxide, silicon nitride, silicon oxynitride, silicon oxide carbide, silicon oxycarbonitride, silicon carbide, fluorine-containing silicon oxide, and fluorine-containing silicon carbide; aluminum-based compounds such as aluminum oxide, aluminum nitride, aluminum oxynitride, and aluminum oxide carbide; niobium-based compounds such as niobium oxide; zinc-based compounds such as zinc oxide; titanium-based compounds such as titanium oxide; diamond-like carbon, fluorine-containing diamond-like carbon, and conductive oxides such as ITO and IZO.

[0069] From the viewpoint of increasing the hardness of the laminate and improving the durability of the laminate, the inorganic substance-containing layer is preferably a layer containing at least one of diamond-like carbon (DLC), silicon oxide, niobium oxide, silicon carbide oxide, and silicon carbide as an inorganic substance among the above, and more preferably a layer containing at least one of DLC, silicon oxide, and niobium oxide. Among these, the inorganic substance-containing layer is more preferably a DLC layer formed of diamond-like carbon (DLC). By using DLC, the film stress generated during the formation of the inorganic substance-containing layer (1) tends to increase, making it easier to form a wrinkle structure.

[0070] [Cover resin layer] The cover resin layer is preferably formed on the resin layer by a dry process described later. The cover resin layer is a layer formed of a resin component and contains the resin component as a main component. Here, containing the resin component as a main component means that the resin component accounts for 50% by mass or more of the cover resin layer, preferably 70% by mass or more, preferably 80% by mass or more, preferably 90% by mass or more, and preferably 100% by mass.

[0071] As the resin component used for the cover resin layer, a resin component that can be formed on the resin layer by a dry process can be preferably used. Specific resin components include fluororesin, polyethylene, polystyrene, etc., and among them, a fluororesin layer formed by a fluororesin is preferred. By using a fluororesin, the cover resin layer can be easily formed on the resin layer by a dry process. In addition, by using a fluororesin, when the cover resin layer is the outermost surface, it becomes easier to impart chemical resistance, slipperiness, or liquid repellency to the laminate. Examples of the fluorine-based resin include polytetrafluoroethylene and tetrafluoroethylene-ethylene copolymer.

[0072] [Cover layer formation] The cover layer is preferably formed by a dry process as described below, but is not necessarily required to be formed by a dry process. If the cover layer is not formed by a dry process, unevenness including a wrinkle structure may be formed in the resin layer in advance by a separate dry process, and then the cover layer may be formed.

[0073] [Cover layer thickness] The thickness (ta) of the cover layer is preferably 5 nm or more and 300 nm or less. By setting the thickness (ta) of the cover layer within the above range, an appropriate film stress is generated when the film is formed by a dry process, and an appropriate compressive stress is applied to the resin layer, making it easy to form a wrinkle structure with a desired roughness. From the viewpoint of making it easy to form a desired unevenness on the outermost surface of the laminate, the thickness (ta) of the cover layer is more preferably 10 nm or more and 250 nm or less, and even more preferably 20 nm or more and 200 nm or less.

[0074] [Thickness ratio of cover layer to resin layer (ta / tb)] In the present invention, the ratio (ta / tb) of the thickness of the cover layer (ta, unit: nm) to the thickness of the resin layer (tb, unit: μm) is preferably 0.1 or more and 3500 or less. By setting the thickness ratio within the above range, when the cover layer is formed by a dry process, it becomes easier to form irregularities with a wrinkle structure of the desired roughness by the dry process. In addition, when irregularities including a wrinkle structure are formed on the surface of the resin layer before the cover layer is formed, the cover layer can prevent the unevenness from being smoothed. From the viewpoint of easily forming the desired irregularities on the outermost surface of the laminate, the thickness ratio is more preferably 1 or more and 500 or less, more preferably 2 or more and 400 or less, and even more preferably 5 or more and 250 or less.

[0075] <Method of manufacturing laminate> The laminate of the present invention may be produced by any production method, but a production method of a laminate according to one embodiment of the present invention includes the following steps 1 to 3. Step 1: A step of applying a curable resin composition to at least one surface of a substrate to form a resin layer precursor. Step 2: Semi-curing the resin layer precursor formed in step 1 Step 3: A step of further performing a surface treatment by a dry process on the resin layer precursor semi-cured in step 2 to form irregularities including a wrinkle structure on one side of the surface of the base material. However, step 2 may be omitted as described below, and therefore in step 3, the uncured resin layer precursor may be subjected to a surface treatment. Each step will now be described in more detail.

[0076] [Process 1] In step 1, a curable resin composition is applied to at least one surface of a substrate to form a resin layer precursor. The details of the curable resin composition used in step 1 are as described above. The curable resin composition may be diluted with a solvent such as water or an organic solvent as necessary. When diluted with a solvent such as water or an organic solvent, the amount (parts by mass, etc.) of the curable resin composition described above and the amount of each component constituting the composition are based on the solid content. The organic solvent to be used is not particularly limited, and may be selected from the viewpoint of solubility, dispersibility, etc. depending on the composition of the curable resin composition. Examples of the organic solvent include alcohol-based solvents such as methyl alcohol, ethyl alcohol, isopropyl alcohol, etc.; ether-based solvents such as dimethyl glycol, ethylene glycol monoethyl ether, etc.; ester-based solvents such as ethyl acetate, etc.; acetate-based solvents such as propylene glycol monomethyl ether acetate, etc.; ketone-based solvents such as methyl isobutyl ketone, methyl ethyl ketone, etc.; aliphatic hydrocarbon-based solvents such as various alkanes, etc.; and aromatic hydrocarbon-based solvents such as toluene, xylene, benzene, etc. The organic solvent may be one type or two or more types, if necessary. The components constituting the curable resin composition may be dissolved in the solvent or may be dispersed in the solvent. When the curable resin composition is diluted with water, an organic solvent, or the like, it is preferable to adjust the solid content concentration to, for example, about 0.1% by mass or more and 50% by mass or less, preferably about 3% by mass or more and 40% by mass or less.

[0077] The curable resin composition can be applied to a substrate by any of the conventional coating methods such as reverse gravure coating, direct gravure coating, roll coating, die coating, bar coating, curtain coating, spray coating, dip coating, and spin coating. When the substrate is a resin film, the curable resin composition may be applied by in-line coating, which refers to applying the curable resin composition on the production line in which the resin film is formed. The solvent after coating can be dried by heating in an oven or by non-heating using a reduced pressure dryer. The surface of the substrate to which the curable resin composition is applied may be previously subjected to a surface treatment such as a corona treatment, a plasma treatment, or a UV ozone treatment.

[0078] [Process 2] In step 2, the curable resin composition in the resin layer precursor formed in step 1 is brought into a semi-cured state. The term "semi-cured" as used herein refers to a state in which the curable resin composition is not completely cured, and refers to a state in which the curing of the curable resin composition further progresses when further exposed to heat or energy rays. Whether the curable resin composition is semi-cured or not can be confirmed by, for example, rubbing the surface of the resin layer precursor lightly 50 times with a cotton swab soaked in a solvent and checking whether the surface of the substrate is exposed. If the curable resin composition is completely cured, the surface of the substrate will not be exposed even if the surface of the resin layer precursor is rubbed. The degree of semi-curing can be determined from the number of rubs at which the surface of the resin layer precursor begins to thin or the number of rubs until the surface of the substrate is exposed. It is preferable to use the same solvent as the solvent in which the cotton swab is soaked, in which the curable resin composition is diluted.

[0079] The purpose of semi-curing is to make the resin layer precursor obtained in step 1 in a state that is easy to handle before being brought into the vacuum drying process in step 3, and to control the wrinkle structure formed in step 3. Therefore, for example, if the resin layer precursor obtained in step 1 is very tacky and difficult to handle, it is preferable to perform a semi-curing treatment, but if there are no problems with handling, step 2 is not essential and heating or energy ray irradiation may not be necessary. Furthermore, by bringing the curable resin composition into a semi-cured state, the resin layer precursor is more likely to buckle during the surface treatment by the dry process in step 3, and unevenness including a wrinkle structure is more likely to be formed.

[0080] When the curable resin composition has thermosetting properties, in this step 2, the resin layer precursor formed in the above step 1 is semi-cured by heating. The method of semi-curing the resin layer precursor may be performed at room temperature such as natural drying, but from a practical standpoint, it is preferable to perform it by heating such as heat drying. In addition, when the drying of the solvent in step 1 is performed by heat drying, the drying of the solvent may also serve as this step 2. Furthermore, in the case where the curable resin composition has active energy ray curability, in this step 2, the resin layer precursor formed in step 1 is semi-cured by irradiating the resin layer precursor with active energy rays. However, in the case where a heat and active energy ray curable resin composition is used as the resin layer component, the resin layer precursor may be semi-cured only by heating or only by irradiating with active energy rays, or the resin layer precursor may be semi-cured by a combination of heating and irradiating with active energy rays.

[0081] When the resin layer precursor is semi-cured by heating, the heating temperature and heating time may be set according to the components contained in the curable resin composition, and the resin layer precursor is heated, for example, at a temperature of 50°C or more and 200°C or less, preferably 70°C or more and 150°C or less, for example, for a time of 3 seconds or more and 30 minutes or less, preferably 30 seconds or more and 10 minutes or less, and more preferably 40 seconds or more and 5 minutes or less.

[0082] In addition, when the resin layer precursor is semi-cured by irradiating with active energy rays, the active energy rays that can be used include light rays such as far ultraviolet rays, ultraviolet rays, near ultraviolet rays, and infrared rays, electromagnetic waves such as X-rays and gamma rays, as well as electron beams, proton beams, and neutron beams. However, curing by ultraviolet irradiation is advantageous in terms of curing speed, ease of availability of irradiation equipment, cost, and the like. When the resin layer precursor is semi-cured by ultraviolet irradiation, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a carbon arc lamp, a metal halide lamp, a xenon lamp, a chemical lamp, an electrodeless discharge lamp, an LED lamp, or the like that emits light in the wavelength range of 150 to 450 nm may be used. The ultraviolet light may be irradiated to such an extent that the resin layer precursor is semi-cured, and the irradiation amount is not particularly limited, but may be, for example, 0.5 to 5000 mJ / cm. 2 , preferably 1 to 2000 mJ / cm 2 It is sufficient to irradiate ultraviolet light with an integrated light quantity of about 100 nm.

[0083] [Process 3] In step 3, the semi-cured resin layer precursor or the uncured resin layer precursor in step 2 is further subjected to surface treatment by a dry process to form irregularities including a wrinkle structure on one side of the surface of the substrate. In step 3, a cover layer may be formed by a dry process, but a dry process treatment without forming a film may be performed without forming a cover layer. The dry process is a technique for performing a surface treatment on a semi-cured or uncured resin layer precursor under reduced pressure or in vacuum.

[0084] In this embodiment, the principle by which the unevenness including the wrinkle structure is formed by the surface treatment using a dry process is not clear, but is presumed to be as follows. When a cover layer is formed on a semi-cured or uncured resin layer precursor by a dry process, it is considered that the resin layer precursor receives energy from the dry process (light from plasma, radiant heat, electrons and ions, or energy from incident particles) and hardens. At that time, the resin layer precursor that has received energy from the dry process increases in temperature and hardens, shrinks, and loses fluidity, and the cover layer grows and generates film stress. During this process, the compressive stress along the surface direction of the resin layer precursor increases, and it is presumed that buckling occurs when the resin layer precursor can no longer resist the compressive stress, forming a wrinkle structure. Furthermore, even in the case of a dry process that does not form a cover layer or involve film formation, it is presumed that the energy from the dry process treatment similarly generates compressive stress along the surface direction in the resin layer precursor, and when the resin layer precursor can no longer resist the compressive stress, buckling occurs and a wrinkle structure is formed.

[0085] In this embodiment, when the total amount of solids in the resin layer is taken as 100 mass %, the organic particles or inorganic particles are contained in an amount of 1 to 25 mass %. If the resin layer contains more than 25% by mass of organic or inorganic particles, the particles are more likely to aggregate during the drying process of the coating film. When this particle aggregation occurs, the particles move, dragging the surrounding resin layer components with them, causing the resin layer to become thinner in parts, and it is believed that the unevenness including the wrinkle structure as shown in Figures 7 and 8 is not formed in parts.

[0086] The uneven state of the outermost surface of the laminate (i.e., surface roughness (Sa, Sz), specific surface area S / A, etc.) is presumed to change depending on the thickness of the resin layer and cover layer, the hardness of the resin layer precursor in a semi-cured or uncured state, the balance of resin fluidity, and the content and dispersion state of particles in the resin layer. Therefore, the uneven state of the outermost surface of the laminate can be adjusted by appropriately changing the thickness of the resin layer and cover layer, the components contained in the resin layer and cover layer (e.g., the content and dispersion state of particles in the resin layer), and the curing conditions, etc. Furthermore, the surface treatment by the dry process is for promoting the curing of the resin layer precursor as described above, and the resin layer may be fully cured, for example, in step 3. Full curing means a state in which curing does not substantially proceed even when the resin layer is heated or irradiated with active energy rays.

[0087] In this manufacturing method, it is preferable to form the cover layer by surface treatment using a dry process. When the cover layer is formed by surface treatment using a dry process, membrane stress occurs as described above, making it easier to form a wrinkle structure. In addition, by forming the cover layer by surface treatment using a dry process, the cover layer can be formed while forming the unevenness including the wrinkle structure in step 3, thereby simplifying the process. Whether or not a dry process has been performed can be determined by observing the cross section with a SEM and / or a TEM. For example, if the cover layer is made of a crystalline material, if the crystal grain size changes in the thickness direction of the cover layer, it can be determined that a dry process has been performed. As the film formation by the dry process progresses, the crystal nuclei generated on the surface of the resin layer grow and the grain size gradually increases, so that the crystal grain size on the surface of the cover layer is the largest, and the crystal grain size tends to become smaller as it approaches the resin layer. On the other hand, such changes in crystal grain size are not observed when wet processing is performed by applying a solvent. In the case of wet processing, the solvent evaporates during the drying process of the coating, which tends to cause tiny voids throughout the thickness of the cover layer, resulting in a low-density film.

[0088] When the cover layer is formed by surface treatment using a dry process, examples of the surface treatment using the dry process include chemical vapor deposition (CVD) and physical vapor deposition (PVD). The dry process is preferably a process carried out under vacuum or reduced pressure. When the surface treatment is carried out under vacuum or reduced pressure, the semi-cured or uncured resin layer precursor is placed in an atmosphere with less oxygen, and the curing is facilitated by the dry process. Therefore, when the dry process is carried out under vacuum or reduced pressure, a wrinkle structure is easily formed. In particular, in the case of an active energy ray-curable resin composition, oxygen inhibition that hinders radical polymerization is suppressed, and crosslinking is facilitated. The pressure in the dry process carried out under vacuum or reduced pressure depends on the method of the dry process, but is, for example, 15 Pa or less, preferably 10 Pa or less, and more preferably 1 Pa or less. The lower limit of the pressure in the dry process is not particularly limited, but considering the performance limit of each device, it is, for example, 1×10 -7 It is Pa.

[0089] The CVD is not particularly limited, and may be plasma CVD, thermal CVD, cat-CVD (catalyzed chemical vapor deposition), etc., but plasma CVD is preferred. By using plasma CVD, it becomes easier to form a wrinkle structure. From the viewpoint of facilitating the formation of a wrinkle structure, CVD is preferably performed under reduced pressure, and the pressure when forming the cover layer is preferably 15 Pa or less, more preferably 1×10 -2 Pa or more and 10 Pa or less, more preferably 1×10 -1 Pa or more and 1 Pa or less.

[0090] The output conditions when forming the cover layer are preferably 100 W or more and 1500 W or less, more preferably 300 W or more and 1200 W or less, and even more preferably 400 W or more and 1000 W or less, from the viewpoint of generating a necessary and sufficient film stress in the cover layer. The thickness of the cover layer can be adjusted by a known method. For example, when plasma CVD is used, the thickness can be adjusted by adjusting the output, pressure of the source gas, concentration of the source gas, plasma generation time, etc. When the surface treatment is carried out by CVD, the cover layer may be subjected to a crosslinking treatment by electron beam irradiation, if necessary, in order to improve water resistance and durability.

[0091] CVD is preferably used, for example, when forming an inorganic-substance-containing layer or a cover resin layer, and can be particularly suitably used when forming an inorganic-substance-containing layer that contains DLC as an inorganic substance, an inorganic-substance-containing layer that contains silicon carbide and / or silicon oxide as an inorganic substance, or a fluororesin layer that contains a fluororesin or the like as a resin component.

[0092] Examples of PVD include vacuum deposition, sputtering, ion plating, etc., and among these, vacuum deposition and sputtering are preferred. PVD is suitable, for example, when the inorganic substance contained in the inorganic substance-containing layer is a metal, a metal oxide such as niobium oxide or silicon oxide, or a metal nitride. Vacuum deposition is also suitable when the inorganic substance contained in the inorganic substance-containing layer is a metal such as gold, silver, copper, or aluminum, a metal oxide such as silicon oxide, titanium oxide, or aluminum oxide, or a fluoride such as calcium fluoride, while sputtering is also suitable when the inorganic substance contained in the inorganic substance-containing layer is a metal such as gold, silver, copper, or aluminum, or a metal oxide such as titanium oxide, aluminum oxide, niobium oxide, ITO, or IZO.

[0093] The pressure when forming the cover layer by PVD is preferably 1×10 -7 Pa or more and 20 Pa or less, more preferably 1×10 -6 Pa or more and 10 Pa or less, more preferably 1×10 -4 Pa or more and 5 Pa or less.

[0094] When the cover layer is formed by surface treatment using a dry process, a raw material for forming the cover layer may be appropriately selected and then the dry process may be carried out. For example, when forming an inorganic material-containing layer containing DLC ​​as an inorganic material by CVD, it is preferable to use a hydrocarbon as a raw material. 4n+6 H 4n+12(n is an integer of 1 or more), for example, alicyclic hydrocarbons such as adamantane, diamantane, triamantane, pentamantane, tetramantane, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., aliphatic hydrocarbons such as acetylene, ethylene, propylene, methane, ethane, propane, etc., may be used. These raw materials may be used alone or in combination of two or more. The raw material gas may be used by diluting it with a rare gas such as argon (Ar) or helium (He). Of course, the inorganic-containing layer including DLC ​​may be formed by PVD.

[0095] For example, when forming an inorganic-containing layer containing silicon carbide as an inorganic substance by CVD, it is preferable to use organosilanes such as tetramethylsilane and hexamethyldisilane as raw materials. Hydrogen gas may also be mixed into a mixed gas of a silicon component such as silane or disilane and a carbon component such as an alkane having 1 to 6 carbon atoms. However, other raw materials may be used as long as silicon carbide can be formed. Furthermore, for example, when forming a fluororesin layer by CVD, CF 4 , C 2 F 4 , C 2 F 6 , C 3 F 8 , C 4 F 8 , C 5 F 8 A fluorine-based gas such as

[0096] Furthermore, for example, when forming an inorganic-containing layer containing silicon carbide oxide as an inorganic material by CVD, a silicon compound (hereinafter also referred to as "silicon compound raw material") may be used as a raw material. The silicon compound raw material may be used in any state of gas, liquid, or solid at room temperature and normal pressure. In the case of gas, it may be introduced directly into the reactor (for example, the discharge space). In the case of liquid or solid, it may be vaporized by means of heating, bubbling, decompression, ultrasonic irradiation, or the like before use. It may also be used after dilution with a solvent, and the solvent may be an organic solvent such as methanol, ethanol, or n-hexane, or a mixture thereof.

[0097] Examples of the silicon compound raw material include silane, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, tetraisopropoxysilane, tetra-n-butoxysilane, tetra-t-butoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diethyldimethoxysilane, diphenyldimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, phenyltriethoxysilane, (3,3,3-trifluoropropyl)trimethoxysilane, hexamethoxysilane, tetraisoprop ... Tyldisiloxane, bis(dimethylamino)dimethylsilane, bis(dimethylamino)methylvinylsilane, bis(ethylamino)dimethylsilane, N,O-bis(trimethylsilyl)acetamide, bis(trimethylsilyl)carbodiimide, diethylaminotrimethylsilane, dimethylaminodimethylsilane, hexamethyldisilazane, hexamethylcyclotrisilazane, heptamethyldisilazane, nonamethyltrisilazane, octamethylcyclotetrasilazane, tetrakis(dimethyla (amino)silane, tetraisocyanatosilane, tetramethyldisilazane, tris(dimethylamino)silane, triethoxyfluorosilane, allyldimethylsilane, allyltrimethylsilane, benzyltrimethylsilane, bis(trimethylsilyl)acetylene, 1,4-bistrimethylsilyl-1,3-butadiyne, di-t-butylsilane, 1,3-disilabutane, bis(trimethylsilyl)methane, cyclopentadienyltrimethylsilane, phenyldimethylsilane, phenyltrimethylsilane Examples of suitable methylsilane include methylsilane, propargyltrimethylsilane, tetramethylsilane, trimethylsilylacetylene, 1-(trimethylsilyl)-1-propyne, tris(trimethylsilyl)methane, tris(trimethylsilyl)silane, vinyltrimethylsilane, hexamethyldisilane, octamethylcyclotetrasiloxane, tetramethylcyclotetrasiloxane, hexamethylcyclotetrasiloxane, and methyl silicate (for example, "Methyl Silicate 51" manufactured by Colcoat Co., Ltd.).

[0098] A cover layer may not be formed in the surface treatment by the dry process in step 3. The surface treatment in the case where a cover layer is not formed is not particularly limited as long as the resin layer precursor can be buckled by the surface treatment to form unevenness including a wrinkle structure, and examples of the surface treatment include plasma treatment. The plasma treatment is not particularly limited, and may be performed by a method such as vacuum or reduced pressure plasma treatment, among which vacuum plasma treatment is preferred. The plasma treatment may be performed by converting a gas into plasma. Examples of the gas used include oxygen gas, hydrogen gas, nitrogen gas, and rare gases such as argon and helium. The gas may be one of these gases, or two or more types of gases may be mixed together. Among these, argon is preferred.

[0099] In this embodiment, the resin layer precursor that has not yet been sufficiently cured is subjected to surface treatment by a dry process as described above. Therefore, in order to stably form a wrinkle structure, it is preferable to adjust the time and storage temperature until the resin layer precursor is semi-cured (step 2) and then moved to the surface treatment by a dry process (step 3). The interval between step 2 and step 3 (i.e., the time from the end of heating and / or active energy ray irradiation to the start of surface treatment by the dry process) is not particularly limited as long as the resin layer precursor is in a desired semi-cured state when the surface treatment is started, but is, for example, 24 hours or less, preferably 10 hours or less, and more preferably 5 hours or less. The lower limit of the interval is not particularly limited, and may be 0 minutes or more. The interval between step 2 and step 3 is not particularly limited, but the substrate on which the resin layer precursor is formed may be left at a temperature of, for example, 0°C or higher and 40°C or lower, preferably 5°C or higher and 30°C or lower. Furthermore, when the interval time is long, the heating conditions and the active energy ray irradiation conditions in step 2 may be appropriately selected taking into consideration that curing progresses between step 2 and step 3.

[0100] In this manufacturing method, by carrying out the above steps 1 to 3, or steps 1 and 3, a resin layer and a cover layer are formed on the substrate, and unevenness including a wrinkle structure can be formed on the surface of the resin layer or the surface of the cover layer.

[0101] [Step 4] This production method may further include the following step 4 after the above steps 1 to 3, or after steps 1 and 3. Step 4: Forming a cover layer on one side of the substrate that has been surface-treated in step 3 This manufacturing method includes step 4, which allows a cover layer to be formed on the resin layer that has been subjected to the above-mentioned surface treatment.

[0102] In step 4, the cover layer can be formed in the same manner as the method for forming the inorganic substance-containing layer and the resin layer in step 3, that is, the inorganic substance-containing layer and the resin layer can be formed by surface treatment using a dry process. The specific method for forming each of these layers is the same as that described in step 3, and therefore the description thereof will be omitted. In step 4, the cover layer can also be formed by a method other than the dry process. For example, a coating liquid containing an inorganic substance, a resin component, or an inorganic substance and a resin component can be applied to one side of the substrate to form a coating film, and the coating film can be dried, cured, or the like as necessary.

[0103] <Applications of laminates> The laminate of the present invention can be suitably used for packaging food, daily necessities, industrial products, medicines, etc. Specifically, it can be used as packaging materials such as various containers, such as bottle containers and pouch containers, for food, cosmetics, daily necessities such as shampoo and rinse, medicines, various industrial products, etc., and films. In packaging materials, it can be suitably used as a component for preventing adhesion of contents by imparting water repellency and oil repellency. The laminate can also be used as an optical material. Examples of optical materials include window glass, lenses, substrates, etc. In optical materials, the unevenness of the wrinkle structure can be used to impart cloudiness to the optical material, thereby controlling the haze and light transmittance of the optical material.

[0104] The laminate of the present invention may have a coating layer on the cover layer that is the outermost surface of the laminate, depending on the application, to the extent that the effect of the present invention is not impaired. For example, in an application for preventing adhesion, a coating layer having a liquid repellent effect can be provided to impart adhesion prevention to the surface of the laminate.

[0105] <Explanation of terms> In the present invention, the term "film" includes the term "sheet", and the term "sheet" includes the term "film". EXAMPLES

[0106] The present invention will be specifically described below with reference to examples, although the present invention is not limited to the following examples in any way. The measurement and evaluation methods used in the present invention are as follows.

[0107] (1) Method for measuring the thickness of the resin layer The surface of the resin layer is treated with RuO 4 The sections were then stained with RuO and embedded in epoxy resin. 4 After staining, the cross section of the resin layer was measured using a TEM (Hitachi High-Technologies Corporation "H-7650", accelerating voltage 100 kV). The thickness was determined by the average value of the maximum thickness and the minimum thickness in the portion where no particles were present.

[0108] (2) Method for measuring the thickness of the cover layer Samples were prepared by epoxy resin embedding ultrathin sectioning and measured using a cross-sectional TEM (JEM-1200EXII, manufactured by JEOL Ltd.) at an accelerating voltage of 120 kV.

[0109] (3) Sa (arithmetic mean roughness), Sz (maximum height) and specific surface area (S / A) The Sa, Sz, and specific surface area (S / A) of the outermost surface of the laminate were measured using a three-dimensional non-contact surface shape measuring device (VertScan2.0 R5200G, manufactured by Ryoka Systems Co., Ltd.) The measurements were performed in an area of ​​496.17 μm × 351.89 μm using a 10x objective lens. In the specific surface area (S / A), A represents the area of ​​the area to be measured, S represents the surface area of ​​the area to be measured, and S / A represents the specific surface area of ​​the area to be measured.

[0110] (4) Measurement of bias In accordance with ISO25178, the deviation Ssk of the outermost surface of the laminate obtained by the method described in the specification was measured.

[0111] (5) Measurement of Kurtosis In accordance with ISO25178, the sharpness Sku of the outermost surface of the laminate obtained by the method described in the specification was measured.

[0112] (6) Surface observation The outermost surface of the laminate on one side of the substrate was photographed at 1,000 times magnification using a scanning microscope (Hitachi High-Tech Corporation, "Regulus SU8220") to obtain an observation image of 60 μm × 40 μm. When irregular wrinkle-like unevenness (unevenness of wrinkle structure) was observed, it was evaluated as A (good), and when no unevenness of wrinkle structure was observed, it was evaluated as B (poor). In addition, in the same observation image, when the particles were not agglomerated but were well dispersed and the unevenness of the wrinkle structure was well formed, it was rated as S (very good); when the particles were slightly agglomerated but the unevenness of the wrinkle structure was well formed, it was rated as A (good); and when the particles were agglomerated and the unevenness of the wrinkle structure was not partially formed, it was rated as B (poor). The observed images of Examples 1 to 4 and Comparative Examples 1 and 2 are shown in FIGS.

[0113] Example 1 (Preparation of Thermosetting Resin Composition (AC1)) A diluted solution of a thermosetting resin composition (AC1) was prepared by adding and mixing 2.12 parts by mass of solid content of an acrylic polyol (manufactured by Nippon Shokubai Co., Ltd., product name "UV-G301", ethyl acetate solution with a solid content of 42.4%) as a binder resin, 6.15 parts by mass of an isocyanate compound (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-165N", hexamethylene diisocyanate compound, solid content 100%) as a curing agent, and ethyl acetate as a solvent to a solid content concentration of 21.83% by mass. To the obtained thermosetting resin composition (AC1), acrylic beads (manufactured by Sekisui Chemical Co., Ltd., product name "MBX-12", average particle size 12 μm) as organic particles (P1) were added so that the content of the organic particles was 9.81 mass% when the total solid content was 100 mass%, thereby obtaining the thermosetting resin composition of Example 1.

[0114] (Formation of Resin Layer Precursor) The thermosetting resin composition was applied onto one side of a PET film (manufactured by Mitsubishi Chemical Corporation, product name "T100 type", thickness 188 μm) as a substrate so that the thickness after curing was as shown in Table 1, and heated at 80° C. for 1 minute to dry and cure, thereby forming a semi-cured resin layer precursor. After that, it was left at room temperature (23° C.) for 3 hours, and then the CVD treatment described below was immediately started.

[0115] (Formation of cover layer) Using a plasma CVD device (manufactured by U-TECH Co., Ltd.), acetylene gas was introduced to set the partial pressure to 1 Pa, and CVD was performed at a power of 500 W under a vacuum of 1 Pa to form an inorganic-containing layer (DLC layer) with a thickness of 90 nm on the semi-cured resin layer precursor, thereby obtaining a laminate having a laminate structure of substrate / resin layer / cover layer.

[0116] Examples 2 to 4 The same procedure as in Example 1 was carried out, except that the content of the organic particles and the thickness of the resin layer were changed as shown in Table 1.

[0117] Comparative Examples 1 and 2 The same procedure as in Example 1 was carried out, except that the content of the organic particles and the thickness of the resin layer were changed as shown in Table 1.

[0118] [Table 1]

[0119] As shown in Table 1, in Examples 1 to 4, the particle content in the total solid content of the resin layer was within the range of 1 to 25 mass %, so that the particles did not aggregate and unevenness including a wrinkle structure could be successfully formed. In contrast, in the laminates of Comparative Examples 1 and 2, the particles were aggregated due to the high particle content, and unevenness including a wrinkle structure was not formed partially. [Explanation of symbols]

[0120] 10 Laminate 10A Outer surface of laminate 11 Base material 11A One side of the substrate 12 Resin layer 13 Cover Layer

Claims

1. A laminate comprising a substrate, a resin layer provided on at least one surface of the substrate, and a cover layer provided on and in direct contact with the resin layer, the cover layer is on the outermost surface of the laminate; The resin layer contains organic particles or inorganic particles in an amount of 1 to 25% by mass when the total amount of solids in the resin layer is taken as 100% by mass, an outermost surface of the laminate on the one surface side of the base material has irregularities including a wrinkle structure; the resin layer is a cured product formed by curing a heat or active energy ray curable resin composition, the cover layer is either an inorganic substance-containing layer or a cover resin layer, the inorganic substance-containing layer is formed from at least one metal selected from the group consisting of silicon, zinc, titanium, niobium, gold, silver, copper, indium, tin, and nickel, diamond-like carbon, metal oxides, metal nitrides, metal carbides, and composites thereof; A laminate, wherein the resin component in the cover resin layer is at least one selected from the group consisting of a fluorine-based resin, a polyethylene, and a polystyrene.

2. 2. The laminate according to claim 1, wherein the specific surface area (S / A) of the outermost surface is 1.05 or more.

3. 3. The laminate according to claim 1, wherein the outermost surface has an arithmetic mean roughness (Sa) of 1000 nm or more.

4. The laminate according to any one of claims 1 to 3, wherein the outermost surface has a Sz (maximum height) of 10,000 nm or more.

5. The laminate according to any one of claims 1 to 4, wherein the cover layer is an inorganic substance-containing layer.

6. The laminate according to any one of claims 1 to 5, wherein the inorganic substance-containing layer is formed from at least one selected from the group consisting of diamond-like carbon, metal oxides, metal nitrides, metal carbides, and composites thereof.

7. The laminate according to any one of claims 1 to 6, wherein the cover layer has a thickness (ta) of 5 nm or more and 300 nm or less.

8. The laminate according to any one of claims 1 to 7, wherein the resin layer has a thickness (tb) of 0.1 µm or more and 15 µm or less.

9. 9. The laminate according to claim 1, wherein the organic particles or inorganic particles have an average particle size of 1 μm or more and 30 μm or less.

10. A step of applying a heat or active energy ray curable resin composition to at least one surface of a substrate to form a resin layer precursor; a step of performing a surface treatment by a dry process under vacuum or reduced pressure in which the semi-cured or uncured resin layer precursor is given at least light from plasma, radiant heat, electrons, ions, or energy from incident particles to form a cover layer, and forming irregularities including a wrinkle structure on the surface of one side of the substrate, The curable resin composition contains organic particles or inorganic particles in an amount of 1 to 25% by mass when the total amount of solids in the curable resin composition is taken as 100% by mass, the cover layer is either an inorganic substance-containing layer or a cover resin layer, the inorganic substance-containing layer is formed from at least one metal selected from the group consisting of silicon, zinc, titanium, niobium, gold, silver, copper, indium, tin, and nickel, diamond-like carbon, metal oxides, metal nitrides, metal carbides, and composites thereof; The method for producing a laminate, wherein the resin component in the cover resin layer is at least one selected from the group consisting of a fluorine-based resin, a polyethylene, and a polystyrene.

11. The method for producing a laminate according to claim 10, wherein the surface treatment is any one of chemical vapor deposition, physical vapor deposition, and plasma treatment.

12. A step of semi-curing the resin layer precursor formed by the coating is provided. The method for producing a laminate according to claim 10 or 11, wherein the surface treatment is carried out on the semi-cured resin layer precursor.

Citation Information

Patent Citations

  • Concavo-convex pattern forming sheet and its manufacturing method, reflection preventing body, phase difference plate, process sheet original plate, and method for manufacturing optical element

    JP2008279597A

  • Method for manufacturing original plate sheet and method for manufacturing uneven pattern transfer sheet

    JP2011213053A

  • Decorative synthetic resin molding

    JP2017196900A

  • Water-repellent laminate and method for producing water-repellent laminate

    JP2017226199A

  • Optical body, and window material

    JP2019061026A